Pengaruh Growth Opportunity dan Leverage pada Earning Response Coefficient - Tamara, I Gusti Ayu Ary Amalia; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 30 No 6 (2020), 2020)
The purpose of this research is aim to obtain empirical evidence about the effect of growth opportunity and leverage on earning response coefficient (ERC). This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The sample are selected with purposive sampling method. The number of selected sample are 65 companies. The analysis technique of this research is using multiple linear regression. The result showed that growth opportunity had positive effect on ERC. Whereas leverage had negative effect on ERC. The higher the company's growth rate will increase ERC. While the higher the leverage the company will reduce ERC. Keywords: Growth Opportunity; Leverage; Earning Response Coefficient.